THE USE OF SMALL GROUP DISCUSSION STRATEGY IN TEACHING ENGLISH SPEAKING - Fanny Selvia Rosadi; Cicih Nuraeni; Agus Priadi (Pujangga: Jurnal Bahasa dan Sastra, 2020)
The objective of this research is to answer the question on how small group discussion strategy could improve thestudents speaking skill. The research was conducted at the seventh grade students of SMPN 3 Ciawi in academic year2019/2020. This paper used descriptive qualitative method. The data were collected through observation duringteaching learning process. To add important data and resource, the researchers also did library research and internetresearch. The theory that support this research is based on the theory of Giri in (Rahmat 2017). This research consistsof plans, how to develop and improve students speaking skills ability using small group discussion strategy. It alsocontains the preparation, teaching-learning process and the evaluation. The result of this research indicated that:(1)small group discussion strategy could build confidence of students’ in speaking; (2) engage students in work groupdiscussion communicatively; (3) the students have the opportunities to improve their speaking skills. Keywords: small group discussion, teaching, speakingPenelitian ini bertujuan adalah untuk menjawab pertanyaan bagaimana strategi diskusi kelompok kecil dapatmeningkatkan keterampilan berbicara siswa. Penelitian dilakukan pada siswa kelas VII SMPN 3 Ciawi tahun ajaran2019/2020. Makalah ini menggunakan metode deskriptif kualitatif. Pengumpulan data dilakukan melalui observasiselama proses belajar mengajar. Untuk menambah data dan sumber penting, peneliti juga melakukan studi pustakadan penelusuran internet. Teori yang mendukung penelitian ini didasarkan pada teori Giri dalam (Rahmat 2017).Penelitian ini terdiri atas perencanaan, bagaimana mengembangkan dan meningkatkan kemampuan berbicara siswadengan menggunakan strategi diskusi kelompok kecil. Selain itu juga berisi persiapan, proses belajar-mengajar danevaluasi. Hasil penelitian ini menunjukkan bahwa (1) strategi diskusi kelompok kecil dapat membangun kepercayaandiri siswa dalam berbicara; (2) melibatkan siswa dalam diskusi kelompok kerja secara komunikatif; (3) siswamemiliki kesempatan untuk meningkatkan keterampilan berbicara mereka.Kata kunci: strategi diskusi kelompok kecil, mengajar, berbicara